ANALYSIS OF ALOE VERA PROCESSING BUSINESS INCOME (CASE STUDY OF UMMI HOME INDUSTRY IN MAKASAR DISTRICT, EAST JAKARTA) - Siti Rochaeni; Armaeni Dwi Humaerah; Rafidah Salamah (AGRIBUSINESS JOURNAL, 2021)
The condition of the spread of the aloe vera industry in Indonesia is relatively small and scattered which has high added value, the use of aloe vera as a raw material for cosmetics and medicines can become an export commodity if maximized. Therefore, it is necessary to pay special attention to the aloe vera commodity and its role in improving the economy in the UMKM industry in Indonesia. This study aims to determine the costs incurred and analyze the income in the Ummi Home Industry aloe vera processing business in Makasar District, East Jakarta.  The scope of this study is the aloe vera processing business at Ummi Home Industry, processed products from aloe vera, namely instant aloe vera (powder), nata de aloe (cocktail), and aloe herbal tea. The data processing and analysis methods used in this study are business income analysis, Return Cost ratio (R/C) Analysis, Benefit and Cost ratio (B/C) Analysis, Break Even Point (BEP) Analysis, and Payback Period (PP) Analysis.Based on the feasibility of the aloe vera processing business, the largest R/C ratio value was obtained in the processed aloe vera herbal tea with a capacity of 25 kg of 11.6. The smallest R/C ratio value is in the processed Nata de Aloe capacity of 1 kg of 2.9. The largest production BEP is in processed Instant Aloe Vera (Powder) with a capacity of 50 kg of 50 pcs with a total production of 200 pcs. The smallest production BEP is in processed aloe vera herbal tea with a capacity of 25 kg of 3 pcs with a total production of 35 pcs. The highest price BEP is in processed Instant Aloe Vera (Powder) with a capacity of 1 kg of Rp. 10,990 with a selling price of Rp. 35,000. The lowest price BEP is in the processed aloe vera herbal tea with a capacity of 25 kg of Rp. 1,727 with a selling price of Rp. 20,000. The fastest Payback Period value is found in aloe vera herbal tea products with a PP value of 0.02 years with an input of 25 kg. The longest Payback Period value is found in The Instant Aloe Vera (Powder) product with an average PP of 0.12 years.